“The varieties and unsettled habits of this new land”: Examining Family Strategies in Upper Canada through the Journals of Mary O’Brien - Schuurs, Erin (Ontario History)

(untitled) (The Ontario Historical Society, 2016)
This article argues that Mary O’Brien’s journals highlight her family’s strategy to achieve economic and social security by establishing long-term goals, identifying an advantageous and socially superior position amongst neighbours, and making everyday choices which furthered these goals and advantages. Her account of her life in Upper Canada demonstrates the hidden workings of an agrarian household in a way that is much more personal than a census or tax record. The use of primary sources such as Mary’s journals enables location specific generalizations to be made while examining a larger historical experience. This article is, therefore, concerned with placing the experiences of a farm wife within the context of settlement, class, and labour in the first half of the nineteenth-century.